Low vitamin D levels have become less common in primary hyperparathyroidism. Issue 12 (December 2015) - Walker, M.; Cong, E.; Lee, J.; Kepley, A.; Zhang, C.; McMahon, D.; Bilezikian, J.; Silverberg, S.
Abstract Summary We compared temporal trends in serum 25-hydroxyvitamin D and parathyroid hormone (PTH) in two primary hyperparathyroidism (PHPT) cohorts recruited 20 years apart. The prevalence of 25-hydroxyvitamin D levels <20 and <30 ng/mL declined by 30–50 %, respectively, and was accompanied by lower PTH. In the older cohort, higher PTH may be due to lower 25-hydroxyvitamin D. Introduction Vitamin D deficiency may exacerbate PHPT. Whether there have been temporal trends in 25-hydroxyvitamin D (25OHD) levels in PHPT is unclear. The prevalence of low vitamin D levels (25OHD <20 and <30 ng/mL) and associated biochemical and bone mineral density (BMD) profiles were assessed in two PHPT cohorts recruited over 20 years apart. Methods This is a cross-sectional comparison of serum 25OHD levels, calciotropic hormones, and BMD between two PHPT cohorts recruited at the same hospital: the "old" (N = 103) and "new" (N = 100) cohorts were enrolled between 1984 and 1991 and between 2010 and 2014, respectively. Results Mean 25OHD levels were 26 % higher in the new cohort (23 ± 10 vs. 29 ± 10 ng/mL, p < 0.0001). Levels of 25OHD <20 and <30 ng/mL declined from 46 and 82 %, respectively, to 19 and 54 % (bothp < 0.0001). Supplemental vitamin D use was common in the new (64 %) but not the old cohort (0 %). The new cohort demonstrated 33 % lower serum PTH levels (p < 0.0001). Neither serum nor urine calcium differed. BMD was higher in the new cohort at all skeletal sites (allp < 0.001). Conclusion With the rise in vitamin D supplementation over the last two decades, low 25OHD levels are no longer common in PHPT patients in the New York area. Those with 25OHD <20 and <30 ng/mL have declined by over 50 and 30 %, respectively. The lower mean PTH levels in the new cohort are most likely accounted for by higher vitamin D intake. Whether improved vitamin D status also underlies the relatively higher BMD in the more vitamin D replete cohort of PHPT patients is unknown.